Seawater-corrosion-resistant aluminoferrite cement concrete and preparation method thereof

By using ultrafine steel slag blends and fluorine-containing quaternary ammonium silicane modifiers in ferroalaluminate cement concrete, the problem of insufficient durability of traditional concrete in marine environments is solved, and higher mechanical properties are achieved and corrosion resistance.

CN119462034AActive Publication Date: 2025-02-18TECH SUPERVISION & RES CENT FOR BUILDING MATERIALS IND +1

Patent Information

Application Number
CN202411704068.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-26
Publication Date
2025-02-18
Estimated Expiration
2044-11-26

AI Technical Summary

Technical Problem

Traditional silicate cement concrete is susceptible to corrosion by factors such as salt, climate and biological in the marine environment, resulting in insufficient durability and difficult to meet the needs of long-term use.

Method used

By combining internally mixed steel slag ultrafine blending with fluorine-containing quaternary ammonium silicane modifier, iron aluminate cement concrete that is resistant to seawater erosion was prepared. This method improves the compactness and corrosion resistance of concrete by forming a waterproof layer and reducing the number of chloride ions.

Benefits of technology

The mechanical properties and corrosion resistance of concrete are significantly improved, making it more durable and impermeable in marine environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005154109790000061
    Figure BDA0005154109790000061
  • Figure BDA0005154109790000062
    Figure BDA0005154109790000062
  • Figure BDA0005154109790000111
    Figure BDA0005154109790000111
Patent Text Reader

Abstract

The invention relates to the technical field of building materials, and discloses seawater-corrosion-resistant aluminoferrite cement concrete and a preparation method thereof.The seawater-corrosion-resistant aluminoferrite cement concrete is prepared through the steps that bis [3-(trimethoxysilyl) propyl] amine, perfluorohexyl ethylene and 3-bromopropylene serve as raw materials, addition and quaternization reactions are conducted, the raw materials are polymerized with acrylic acid monomers, and the seawater-corrosion-resistant aluminoferrite cement concrete is obtained. And then compounding with aluminoferrite cement, composite steel slag micro powder, modified basalt fiber and the like to obtain the concrete. The surface of siloxane of the fluorine-containing quaternary ammonium salt siloxane modifier is rich in silicon-oxygen bond functional groups, and the siloxane can be subjected to condensation reaction with silicon hydroxyl on the surface of a concrete base material after being hydrolyzed, so that pores and cracks in a concrete material are effectively filled; the composite steel slag micro-powder admixture is fine in particle, so that the system structure can be filled more tightly, and the capability of hindering permeation and diffusion of Cl <-> ions is improved; the modified basalt fiber improves the dispersion stability in a matrix, and the seawater corrosion resistance of the concrete is further improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of building materials, in particular to a ferroaluminate cement concrete resistant to seawater corrosion and a preparation method thereof. Background Art

[0002] With the large-scale construction of docks, bridges, offshore projects, etc., the adverse effects of seawater on concrete have become apparent, that is, the durability of concrete has become very important; traditional silicate cement concrete has a porous structure, and water and other harmful ions will penetrate into it through the pores. It often shows certain limitations in the marine environment, especially when facing the corrosion of multiple complex factors such as salt, climate, and biology in seawater. Its performance is often difficult to meet the needs of long-term use; ferroaluminate cement, as a new type of cement material, takes anhydrous calcium sulfoaluminate and iron phase as the main minerals to form a series of cements such as fast-hardening, expansion, and self-stress. This cement shows good performance under normal conditions, but its corrosion resistance still has room for improvement in the marine environment.

[0003] At present, the method of adjusting the proportion of cement minerals is usually adopted in engineering to improve the corrosion resistance of ferroaluminate cement concrete. However, adjusting the mineral ratio requires adjusting a series of parameters such as the cement raw material ratio and the firing system, which is too difficult. There are also methods to improve its corrosion resistance by adding other components, such as the combination of expansion agents, mineral admixtures and water reducers. Through the interaction of the above substances, the density of concrete is improved, thereby improving the ability of concrete to resist erosion. However, this type of component only reduces the penetration of chloride ions by increasing the density of concrete. The effective components of some corrosion inhibitors that have the effect of inhibiting the penetration of chloride ions are mostly nitrites, so their scope of application is limited.

[0004] Steel slag is a solid waste produced after artificially adding slag-forming agents in order to clarify molten steel during the steelmaking process. Its mineral composition is similar to that of cement clinker and has certain hydration activity after being ground. Siloxane materials have a smaller molecular structure, and the silicon-oxygen macromolecules formed after hydrolysis and polycondensation are easy to react with the silicon hydroxyl groups on the surface of the concrete substrate, thereby playing a role in compacting the concrete structure. The present invention aims to prepare ferroaluminate cement concrete with excellent seawater corrosion resistance by combining ultrafine steel slag admixtures and infiltrating fluorine-containing quaternary ammonium salt siloxane modifiers, thereby significantly improving the mechanical properties and corrosion resistance of the concrete. Summary of the invention

[0005] The purpose of the present invention is to solve the problems existing in the above-mentioned prior art and provide a seawater erosion-resistant ferroaluminate cement concrete and a preparation method thereof. The ferroaluminate cement has high mechanical strength, seawater scouring resistance and erosion resistance, and can greatly improve the durability of concrete.

[0006] The present invention is achieved through the following technical solutions:

[0007] The invention discloses a ferroaluminate cement concrete resistant to seawater corrosion, comprising the following components in parts by weight: 70-90 parts of ferroaluminate cement, 10-30 parts of composite steel slag powder admixture, 230-280 parts of crushed stone, 180-210 parts of quartz sand, 15-30 parts of fly ash, 5-8 parts of polycarboxylate high-efficiency water reducing agent, 2-5 parts of admixture, 1-5 parts of modified basalt fiber, 2-10 parts of fluorine-containing quaternary ammonium salt siloxane modifier and 40-50 parts of deionized water.

[0008] The preparation method of the composite steel slag micropowder admixture is as follows: steel slag, slag and zeolite are mixed in a mass ratio of 25:65:10, and an appropriate amount of deionized water is added to control the solid content to 40-45%, and an intermittent ball mill is used for grinding at 40-60°C to a median particle size of ≦5μm, carboxymethyl cellulose and an activator are added, and stirred at room temperature for 15-30min to obtain the composite steel slag micropowder admixture; the activator is a mixture of sodium sulfate, triisopropanolamine and silica gel powder, and the mass ratio of the three is 2:2:1.

[0009] Furthermore, the additive is any one of 2-phospho-1,2,4-tricarboxylic acid butane, sodium gluconate, and hydroxyethylidene diphosphonic acid.

[0010] Furthermore, the preparation method of the modified basalt fiber is as follows: 10 g of basalt fiber, 2 g of KH560 and 30 mL of ethanol are uniformly dispersed by ultrasonication, reacted at 60° C. for 3 h, and centrifuged and dried to obtain the modified basalt fiber.

[0011] Further, the preparation method of the fluorine-containing quaternary ammonium salt siloxane modifier is:

[0012] Step (1), under a nitrogen atmosphere, add bis[3-(trimethoxysilyl)propyl]amine and methanol to a reaction flask, stir evenly, add perfluorohexylethylene, stir to react, after the reaction is completed, concentrate under reduced pressure, and dry to obtain a fluorine-containing siloxane monomer.

[0013] Step (2), under nitrogen atmosphere, add fluorinated siloxane monomer and N,N-dimethylformamide to a reaction flask, stir evenly, add 3-bromopropylene, react at 80-100° C. for 16-24 h, cool to room temperature, filter, wash with deionized water, and dry to obtain an alkenyl fluorinated siloxane monomer.

[0014] Step (3), under a nitrogen atmosphere, add methyl methacrylate, acrylic acid, 2-acrylamide-2-methacrylic acid, alkenyl fluorine-containing siloxane monomer and deionized water into a reaction flask, stir evenly, dissolve potassium persulfate in deionized water to prepare an initiator solution with a mass fraction of 30-40%, and add dropwise at a speed of 2-3.5 mL / min. After the addition is completed, react at 70-85° C. for 1-3 h, cool to 35-45° C., add sodium bicarbonate aqueous solution to adjust the pH to neutral, and obtain a fluorine-containing quaternary ammonium salt siloxane modifier.

[0015] Furthermore, in step (1), the molar ratio of bis[3-(trimethoxysilyl)propyl]amine to perfluorohexylethylene is 1:1.05-1.2.

[0016] Furthermore, in step (1), the reaction temperature is 45-60° C. and the reaction time is 5-12 h.

[0017] Furthermore, in step (2), the molar ratio of the fluorinated siloxane monomer to 3-bromopropylene is 1:1.1-1.4.

[0018] Furthermore, in step (3), the mass ratio of methyl methacrylate, acrylic acid, 2-acrylamide-2-methylacrylic acid, alkenyl fluorinated siloxane monomer, and potassium persulfate is 100:10-20:8-15:3-12:4-8.

[0019] Furthermore, the preparation method of ferroaluminate cement concrete resistant to seawater erosion is as follows: pour ferroaluminate cement, composite steel slag powder admixture, crushed stone, quartz sand, and fly ash into a concrete mixer and dry mix for 50-80 seconds. After mixing evenly, add admixtures, polycarboxylate water reducer and deionized water, mix and stir for 5-10 minutes, then add modified basalt fiber and fluorine-containing quaternary ammonium salt siloxane modifier, stir for 10-20 minutes, mix evenly and inject into a mold, vibrate for 20-40 seconds, smooth with a spatula, stand for 16-24 hours, demould, and place in a steam curing box for steam curing to obtain ferroaluminate cement concrete resistant to seawater erosion.

[0020] Furthermore, the steam curing process is to first cure at room temperature for 5-8 hours, then cure at a constant temperature of 50-65°C for 12-16 hours, and finally naturally cure for 7-10 days.

[0021] Compared with the prior art, the present invention has the following beneficial effects:

[0022] The invention uses bis[3-(trimethoxysilyl)propyl]amine, perfluorohexylethylene and 3-bromopropylene as raw materials, obtains alkenyl fluorine-containing siloxane monomers through addition and quaternization reactions, and polymerizes with acrylic monomers to obtain fluorine-containing quaternary ammonium salt siloxane modifiers, which are then compounded with ferroaluminate cement, composite steel slag powder and modified basalt fiber to obtain ferroaluminate cement concrete resistant to seawater erosion.

[0023] (1) Fluorine-containing quaternary ammonium salt siloxane modifiers contain organic fluorine and organic silicon with good hydrophobic properties, which can form a waterproof layer on the surface of concrete, preventing the entry of corrosive factors in a physical barrier manner; the positive charge of the quaternary ammonium salt cation can adsorb with the free chloride ions in the concrete to form a stable compound, reducing the number of free chloride ions in the concrete, thereby reducing the risk of chloride ion corrosion to the concrete; the alkoxy group in the siloxane can undergo a condensation reaction with the silanol group on the surface of the concrete substrate after being hydrolyzed into hydroxyl groups, forming a tetrahedral Si-O-Si covalent bond, thereby cross-linking into a dense hardened microstructure; the surface of the fluorine-containing quaternary ammonium salt siloxane modifier has a relatively rich Si-O bond functional group, which will tightly cross-link the hydration products together after combining with the ferroaluminate cement-based material to form a dense grid structure, thereby improving the bonding strength between the hydration products and effectively filling the pores and cracks in the concrete material, thereby improving the mechanical properties and durability of the concrete.

[0024] (2) The composite steel slag powder admixture has fine particles, smooth surface and high dispersion, which is beneficial to improve the fluidity of fresh concrete and can fully fill the pores and capillary channels of hardened concrete and compact concrete. It can react with Ca(OH) produced by cement hydration. 2 Secondary reaction occurs, filling the pores and blocking the capillary channels, making the pore size of the cement fly ash slurry finer, the pore tortuosity increased, and the connected pores reduced. The addition of steel slag-based composite admixtures makes the system composed of complex particles. Compared with single cement particles, particles of different sizes enter the concrete, changing the pore structure of the concrete, reducing its porosity and making the pore distribution more uniform, which can make the system structure more densely filled, thereby improving the concrete barrier Cl - The ability of ions to penetrate and diffuse.

[0025] (3) The modified basalt fiber is modified by KH560, which increases its specific surface area, reduces the interfacial tension, improves the dispersion stability in the matrix, and improves the compatibility and bonding between it and the concrete; the steel slag-based composite admixture, fluorine-containing quaternary ammonium salt siloxane modifier and modified basalt fiber have a synergistic effect, forming a spatial network structure, which can make the structure of concrete more compact and increase the concrete's impermeability, thereby improving the concrete's impermeability and corrosion resistance, and further broadening the application range of concrete. DETAILED DESCRIPTION

[0026] The technical scheme in the embodiment of the present invention will be clearly and completely described below. Obviously, the described embodiment is only a part of the embodiment of the present invention, rather than all embodiments. Based on the embodiment in the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work premise belong to the scope of protection of the present invention. Unless otherwise specified, the raw materials and reagents used in this application are all commercially available products, or can be prepared by known methods.

[0027] Preparation of composite steel slag micropowder admixture: steel slag, slag and zeolite are mixed in a mass ratio of 25:65:10, and an appropriate amount of deionized water is added to control the solid content to 40-45%, and an intermittent ball mill is used for grinding at 40-60°C to a median particle size of ≦5μm, carboxymethyl cellulose and an activator are added, and stirred at room temperature for 15-30 minutes to obtain a composite steel slag micropowder admixture; the activator is a mixture of sodium sulfate, triisopropanolamine and silica gel powder, and the mass ratio of the three is 2:2:1.

[0028] The preparation method of the modified basalt fiber is as follows: 10 g of basalt fiber, 2 g of KH560 and 30 mL of ethanol are uniformly dispersed by ultrasonication, reacted at 60° C. for 3 h, and centrifuged and dried to obtain the modified basalt fiber.

[0029] Bis[3-(trimethoxysilyl)propyl]amine, CAS number is 82985-35-1.

[0030] Perfluorohexylethylene, CAS number is 25291-17-2.

[0031] 3-Brompropylene, CAS number is 106-95-6.

[0032] Example 1

[0033] (1) Under nitrogen atmosphere, 45 mmol of bis[3-(trimethoxysilyl)propyl]amine and 270 mL of methanol were added to a reaction flask, and after stirring, 52.2 mmol of perfluorohexylethylene was added, and the mixture was reacted at 55° C. for 8 h, and then concentrated under reduced pressure and dried to obtain a fluorinated siloxane monomer. The preparation reaction formula is as follows:

[0034]

[0035] (2) Under nitrogen atmosphere, 42 mmol of fluorinated siloxane monomer and 420 mL of N,N-dimethylformamide were added to the reaction flask, and after stirring, 48.3 mmol of 3-bromopropylene was added, and the mixture was reacted at 90° C. for 18 h, cooled to room temperature, filtered, washed with deionized water, and dried to obtain an alkenyl fluorinated siloxane monomer. The preparation reaction formula is as follows:

[0036]

[0037] (3) Under a nitrogen atmosphere, 100 g of methyl methacrylate, 15 g of acrylic acid, 12 g of 2-acrylamide-2-methacrylic acid, 3 g of alkenyl fluorinated siloxane monomer and 40 mL of deionized water were added to a reaction flask. After stirring, 5 g of potassium persulfate was dissolved in deionized water to prepare an initiator solution with a mass fraction of 35%, and the solution was added dropwise at a rate of 2.5 mL / min. After the addition was completed, the mixture was reacted at 75° C. for 2 h, cooled to 30° C., and a sodium bicarbonate aqueous solution was added to adjust the pH to neutral to obtain a fluorinated quaternary ammonium salt siloxane modifier.

[0038] (4) 90 g of ferroaluminate cement, 10 g of composite steel slag powder admixture, 260 g of crushed stone, 205 g of quartz sand, and 25 g of fly ash were poured into a concrete mixer and dry mixed for 60 s. After mixing evenly, 4 g of 2-phospho-1,2,4-tricarboxylic acid butane, 6 g of polycarboxylic acid water reducer, and 45 g of deionized water were added and mixed and stirred for 8 min. Then, 1 g of modified basalt fiber and 2 g of fluorine-containing quaternary ammonium salt siloxane modifier were added and stirred for 15 min. After mixing evenly, the mixture was injected into a mold, vibrated for 30 s, smoothed with a spatula, and demolded after standing for 20 h. The mixture was placed in a steam curing box for steam curing, first at room temperature for 6 h, then at 60°C for 14 h, and finally naturally cured for 7 days to obtain ferroaluminate cement concrete resistant to seawater erosion.

[0039] Example 2

[0040] (1) Under a nitrogen atmosphere, 150 mmol of bis[3-(trimethoxysilyl)propyl]amine and 600 mL of methanol were added to a reaction flask. After stirring, 157.5 mmol of perfluorohexylethylene was added, and the mixture was reacted at 60° C. for 5 h. The mixture was concentrated under reduced pressure and dried to obtain a fluorinated siloxane monomer.

[0041] (2) Under nitrogen atmosphere, 140 mmol of fluorinated siloxane monomer and 1120 mL of N,N-dimethylformamide were added to a reaction flask, and after stirring, 154 mmol of 3-bromopropylene was added, and the mixture was reacted at 100° C. for 16 h. The mixture was cooled to room temperature, filtered, washed with deionized water, and dried to obtain an alkenyl fluorinated siloxane monomer.

[0042] (3) Under a nitrogen atmosphere, 100 g of methyl methacrylate, 10 g of acrylic acid, 8 g of 2-acrylamide-2-methacrylic acid, 5 g of alkenyl fluorinated siloxane monomer and 30 mL of deionized water were added to a reaction flask. After stirring, 4 g of potassium persulfate was dissolved in deionized water to prepare an initiator solution with a mass fraction of 30%, and the solution was added dropwise at a rate of 2 mL / min. After the addition was completed, the mixture was reacted at 85° C. for 1 h, cooled to 45° C., and a sodium bicarbonate aqueous solution was added to adjust the pH to neutral to obtain a fluorinated quaternary ammonium salt siloxane modifier.

[0043] (4) 90 g of ferroaluminate cement, 10 g of composite steel slag powder admixture, 230 g of crushed stone, 180 g of quartz sand, and 30 g of fly ash were poured into a concrete mixer and dry mixed for 50 s. After mixing evenly, 2 g of sodium gluconate, 5 g of polycarboxylate water reducer, and 40 g of deionized water were added and mixed and stirred for 5 min. Then, 2 g of modified basalt fiber and 4 g of fluorine-containing quaternary ammonium siloxane modifier were added and stirred for 10 min. After mixing evenly, the mixture was injected into a mold, vibrated for 20 s, smoothed with a spatula, and demolded after standing for 16 h. The mixture was placed in a steam curing box for steam curing, first at room temperature for 5 h, then at 65°C for 12 h, and finally naturally cured for 8 days to obtain ferroaluminate cement concrete resistant to seawater erosion.

[0044] Example 3

[0045] (1) Under a nitrogen atmosphere, 20 mmol of bis[3-(trimethoxysilyl)propyl]amine and 140 mL of methanol were added to a reaction flask. After stirring, 24 mmol of perfluorohexylethylene was added, and the mixture was reacted at 45° C. for 12 h. The mixture was concentrated under reduced pressure and dried to obtain a fluorinated siloxane monomer.

[0046] (2) Under nitrogen atmosphere, 15 mmol of fluorinated siloxane monomer and 180 mL of N,N-dimethylformamide were added to a reaction flask, and after stirring, 21 mmol of 3-bromopropylene was added, and the mixture was reacted at 80° C. for 24 h. The mixture was cooled to room temperature, filtered, washed with deionized water, and dried to obtain an alkenyl fluorinated siloxane monomer.

[0047] (3) Under a nitrogen atmosphere, 100 g of methyl methacrylate, 20 g of acrylic acid, 15 g of 2-acrylamide-2-methacrylic acid, 7 g of alkenyl fluorinated siloxane monomer and 50 mL of deionized water were added to a reaction flask. After stirring, 8 g of potassium persulfate was dissolved in deionized water to prepare an initiator solution with a mass fraction of 40%, and the solution was added dropwise at a rate of 3.5 mL / min. After the addition was completed, the mixture was reacted at 70° C. for 3 h, cooled to 35° C., and a sodium bicarbonate aqueous solution was added to adjust the pH to neutral to obtain a fluorinated quaternary ammonium salt siloxane modifier.

[0048] (4) 90 g of ferroaluminate cement, 10 g of composite steel slag powder admixture, 280 g of crushed stone, 210 g of quartz sand, and 15 g of fly ash were poured into a concrete mixer and dry mixed for 80 s. After mixing evenly, 5 g of hydroxyethylidene diphosphonic acid, 8 g of polycarboxylic acid water reducer, and 50 g of deionized water were added and mixed and stirred for 10 min. Then, 3 g of modified basalt fiber and 6 g of fluorine-containing quaternary ammonium salt siloxane modifier were added and stirred for 20 min. After mixing evenly, the mixture was injected into a mold, vibrated for 40 s, smoothed with a spatula, and left to stand for 24 h before demolding. The mixture was placed in a steam curing box for steam curing, first at room temperature for 8 h, then at 65°C for 12 h, and finally naturally cured for 9 days to obtain ferroaluminate cement concrete resistant to seawater erosion.

[0049] Example 4

[0050] (1) Under a nitrogen atmosphere, 80 mmol of bis[3-(trimethoxysilyl)propyl]amine and 440 mL of methanol were added to a reaction flask. After stirring, 88 mmol of perfluorohexylethylene was added, and the mixture was reacted at 50° C. for 9 h. The mixture was concentrated under reduced pressure and dried to obtain a fluorinated siloxane monomer.

[0051] (2) Under nitrogen atmosphere, 75 mmol of fluorinated siloxane monomer and 720 mL of N,N-dimethylformamide were added to a reaction flask, and after stirring, 93 mmol of 3-bromopropylene was added, and the mixture was reacted at 95° C. for 20 h. The mixture was cooled to room temperature, filtered, washed with deionized water, and dried to obtain an alkenyl fluorinated siloxane monomer.

[0052] (3) Under a nitrogen atmosphere, 100 g of methyl methacrylate, 16 g of acrylic acid, 14 g of 2-acrylamide-2-methacrylic acid, 10 g of alkenyl fluorinated siloxane monomer and 35 mL of deionized water were added to a reaction flask. After stirring, 7 g of potassium persulfate was dissolved in deionized water to prepare an initiator solution with a mass fraction of 32%, and the solution was added dropwise at a rate of 3 mL / min. After the addition was completed, the mixture was reacted at 80° C. for 3 h, cooled to 30° C., and a sodium bicarbonate aqueous solution was added to adjust the pH to neutral to obtain a fluorinated quaternary ammonium salt siloxane modifier.

[0053] (4) 90 g of ferroaluminate cement, 10 g of composite steel slag powder admixture, 245 g of crushed stone, 190 g of quartz sand, and 25 g of fly ash were poured into a concrete mixer and dry mixed for 65 s. After mixing evenly, 3 g of 2-phospho-1,2,4-tricarboxylic acid butane, 6 g of polycarboxylic acid water reducer, and 48 g of deionized water were added and mixed and stirred for 8 min. Then, 4 g of modified basalt fiber and 8 g of fluorine-containing quaternary ammonium salt siloxane modifier were added and stirred for 15 min. After mixing evenly, the mixture was injected into a mold, vibrated for 35 s, smoothed with a spatula, and left to stand for 24 h for demolding. The mixture was placed in a steam curing box for steam curing, first at room temperature for 6 h, then at 60°C for 15 h, and finally naturally cured for 10 days to obtain ferroaluminate cement concrete resistant to seawater erosion.

[0054] Example 5

[0055] (1) Under a nitrogen atmosphere, 32 mmol of bis[3-(trimethoxysilyl)propyl]amine and 175 mL of methanol were added to a reaction flask. After stirring, 36.8 mmol of perfluorohexylethylene was added, and the mixture was reacted at 50° C. for 12 h. The mixture was concentrated under reduced pressure and dried to obtain a fluorinated siloxane monomer.

[0056] (2) Under a nitrogen atmosphere, 25 mmol of fluorinated siloxane monomer and 255 mL of N,N-dimethylformamide were added to a reaction flask, and after stirring, 32 mmol of 3-bromopropylene was added, and the mixture was reacted at 85° C. for 18 h. The mixture was cooled to room temperature, filtered, washed with deionized water, and dried to obtain an alkenyl fluorinated siloxane monomer.

[0057] (3) Under a nitrogen atmosphere, 100 g of methyl methacrylate, 14 g of acrylic acid, 12 g of 2-acrylamide-2-methacrylic acid, 12 g of alkenyl fluorinated siloxane monomer and 40 mL of deionized water were added to a reaction flask. After stirring, 5 g of potassium persulfate was dissolved in deionized water to prepare an initiator solution with a mass fraction of 35%, and the solution was added dropwise at a rate of 2.5 mL / min. After the addition was completed, the mixture was reacted at 75° C. for 2 h, cooled to 40° C., and sodium bicarbonate aqueous solution was added to adjust the pH to neutral to obtain a fluorinated quaternary ammonium salt siloxane modifier.

[0058] (4) 90 g of ferroaluminate cement, 10 g of composite steel slag powder admixture, 270 g of crushed stone, 205 g of quartz sand, and 25 g of fly ash were poured into a concrete mixer and dry mixed for 75 s. After mixing evenly, 4 g of sodium gluconate, 8 g of polycarboxylate water reducer, and 50 g of deionized water were added and mixed and stirred for 10 min. Then, 5 g of modified basalt fiber and 10 g of fluorine-containing quaternary ammonium siloxane modifier were added and stirred for 20 min. After mixing evenly, the mixture was injected into a mold, vibrated for 30 s, smoothed with a spatula, and demolded after standing for 20 h. The mixture was placed in a steam curing box for steam curing, first at room temperature for 6 h, then at 60°C for 16 h, and finally naturally cured for 10 days to obtain ferroaluminate cement concrete resistant to seawater erosion.

[0059] Comparative Example 1

[0060] (1) Under nitrogen atmosphere, 100 g of methyl methacrylate, 15 g of acrylic acid, 12 g of 2-acrylamide-2-methylacrylic acid, and 3 g of 3-(methacryloyloxy)propyltrimethoxysilane (CAS No. 2530-85-0, structural formula: ) and 40mL of deionized water, stir evenly, dissolve 5g of potassium persulfate in deionized water to prepare an initiator solution with a mass fraction of 35%, and add it dropwise at a rate of 2.5mL / min. After the addition is completed, react at 75°C for 2h, cool to 30°C, add sodium bicarbonate aqueous solution to adjust the pH to neutral, and obtain a siloxane modifier.

[0061] (2) 90 g of ferroaluminate cement, 10 g of composite steel slag powder admixture, 260 g of crushed stone, 205 g of quartz sand, and 25 g of fly ash were poured into a concrete mixer and dry mixed for 60 s. After mixing evenly, 4 g of 2-phospho-1,2,4-tricarboxylic acid butane, 6 g of polycarboxylic acid water reducer, and 45 g of deionized water were added and mixed for 8 min. Then, 1 g of modified basalt fiber and 2 g of siloxane modifier were added and stirred for 15 min. After mixing evenly, the mixture was injected into a mold, vibrated for 30 s, smoothed with a spatula, and demolded after standing for 20 h. The mixture was placed in a steam curing box for steam curing, first at room temperature for 6 h, then at 60 °C for 14 h, and finally naturally cured for 7 days to obtain ferroaluminate cement concrete.

[0062] Comparative Example 2

[0063] (1) Under a nitrogen atmosphere, 100 g of methyl methacrylate, 15 g of acrylic acid, 12 g of 2-acrylamide-2-methylacrylic acid, and 40 mL of deionized water were added to a reaction flask. After stirring, 5 g of potassium persulfate was dissolved in deionized water to prepare an initiator solution with a mass fraction of 35%, and the solution was added dropwise at a rate of 2.5 mL / min. After the addition was completed, the mixture was reacted at 75° C. for 2 h, cooled to 30° C., and a sodium bicarbonate aqueous solution was added to adjust the pH to neutral to obtain an acrylic resin.

[0064] (2) 90 g of ferroaluminate cement, 10 g of composite steel slag powder admixture, 260 g of crushed stone, 205 g of quartz sand, and 25 g of fly ash were poured into a concrete mixer and dry mixed for 60 s. After mixing evenly, 4 g of 2-phospho-1,2,4-tricarboxylic acid butane, 6 g of polycarboxylic acid water reducer, and 45 g of deionized water were added and mixed and stirred for 8 min. Then, 1 g of modified basalt fiber and 2 g of acrylic resin were added and stirred for 15 min. After mixing evenly, the mixture was injected into a mold, vibrated for 30 s, smoothed with a spatula, and demolded after standing for 20 h. The mixture was placed in a steam curing box for steam curing, first at room temperature for 6 h, then at 60 °C for 14 h, and finally naturally cured for 7 days to obtain ferroaluminate cement concrete.

[0065] Comparative Example 3

[0066] 100g of ferroaluminate cement, 260g of crushed stone, 205g of quartz sand and 25g of fly ash were poured into a concrete mixer and dry mixed for 60s. After mixing evenly, 4g of 2-phospho-1,2,4-tricarboxylic acid butane, 6g of polycarboxylate water reducer and 45g of deionized water were added and mixed and stirred for 8min. Then, 1g of modified basalt fiber was added and stirred for 15min. After mixing evenly, the mixture was injected into a mold and vibrated for 30s. The mixture was smoothed with a spatula and allowed to stand for 20h for demoulding. The mixture was placed in a steam curing box for steam curing, first at room temperature for 6h, then at a constant temperature of 60°C for 14h, and finally naturally cured for 7 days to obtain ferroaluminate cement concrete.

[0067] Electric flux test: Referring to GB / T 50082-2009 standard, the concrete was prepared into a sample with a diameter of 100 mm and a height of 50 mm. The electric flux of the concrete sample was tested using a concrete chloride ion electric flux meter. The experimental solution was a 3% NaCl solution.

[0068] Acid and alkali resistance test: The prepared concrete was prepared into specimens with a size of 200mm×200mm×100mm, and immersed in 15% dilute sulfuric acid and sodium hydroxide solution respectively. The liquid level was 30mm higher than the upper surface of the specimen, and the minimum distance between the specimen and the container wall was 30mm. The solution temperature was maintained at 25°C. After 28 days, the specimen was taken out, its surface was cleaned with clean water, and then placed in a standard curing room for 2 days. The surface condition was then taken out and observed.

[0069] Table 1 Corrosion resistance test

[0070]

[0071]

[0072] The smaller the electric flux of concrete, the better the compactness of concrete is, and the better the corrosion of chloride ion environment can be resisted; As can be seen from the test results in the above table, with the increase of the content of fluorine-containing quaternary ammonium salt siloxane modifier, the corrosion resistance of ferroaluminate cement concrete gradually increases, wherein the electric flux in Example 4 is only 330C, with good seawater corrosion resistance; This is because on the one hand, the fluorine-containing quaternary ammonium salt siloxane modifier contains organic fluorine and organic silicon with good hydrophobicity, which can form a waterproof layer on the concrete surface, and prevent the entry of erosion factors in a physical barrier manner; The positive charge of the quaternary ammonium salt cation can adsorb with the free chloride ions in the concrete to form a stable compound, reducing the number of free chloride ions in the concrete, thereby reducing the corrosion risk of chloride ions to the concrete; At the same time, after being hydrolyzed into hydroxyl groups in siloxane, hydrolysis and condensation reactions can occur with the silicon hydroxyl groups on the surface of the concrete substrate to form a tetrahedral Si-O-Si covalent bond, thereby cross-linking into a microstructure of a dense hardened body; On the other hand, the composite steel slag micropowder admixture and the Ca (OH) produced by cement hydration 2 The secondary reaction can fill the pores and block the capillary channels, making the pore size of the cement fly ash slurry finer, the pore tortuosity increased, and the connected pores reduced, thereby improving the concrete barrier Cl - The ability of ion penetration and diffusion. Comparative Example 1 does not contain organic fluorine and quaternary ammonium salt groups, and Comparative Example 2 does not contain organic silicon fluorine and quaternary ammonium salt, and its corrosion resistance is average; Comparative Example 3 does not contain organic modifiers and composite steel slag powder admixtures, and its corrosion resistance is the worst.

[0073] Mechanical properties test: According to GB / T 50081-2019 “Standard for Test Methods for Mechanical Properties of Ordinary Concrete”, the compressive strength and flexural strength of the prepared concrete were tested. The sample size was 100mm×100mm×100mm, and the universal testing machine had a given loading rate of 2.4kN / s.

[0074] Table 2 Compressive strength and flexural strength test

[0075] Compressive strength(MPa) Flexural strength(MPa) Example 1 69.4 5.4 Example 2 77.8 6.1 Example 3 84.5 6.9 Example 4 92.1 7.5 Example 5 93.4 7.6 Comparative Example 1 50.3 5.2 Comparative Example 2 41.7 4.8 Comparative Example 3 35.3 4.2

[0076] The modified basalt fiber is modified by KH560, which increases its specific surface area, reduces the interfacial tension, improves the dispersion stability in the matrix, and improves the compatibility and bonding strength with concrete; the fluorine-containing quaternary ammonium salt siloxane modifier has a relatively rich silicon-oxygen bond functional group on its surface. After combining with the ferroaluminate cement-based material, it will tightly cross-link the hydration products together to form a dense grid structure, improve the bonding strength between the hydration products, and effectively fill the pores and cracks in the concrete material; the steel slag-based composite admixture has fine particles, smooth surface, and high dispersion, which is beneficial to improving the fluidity of fresh concrete and can fully fill and harden the pores and capillary channels of concrete, compact the concrete, thereby improving the mechanical properties and durability of concrete.

[0077] Example 6

[0078] The difference between this embodiment and embodiment 4 is that the addition amount of the composite steel slag powder admixture is 15 g, the addition amount of ferroaluminate cement is 85 g, and other conditions remain the same.

[0079] Example 7

[0080] The difference between this embodiment and embodiment 4 is that the addition amount of the composite steel slag powder admixture is 20 g, the addition amount of ferroaluminate cement is 80 g, and other conditions remain the same.

[0081] Example 8

[0082] The difference between this embodiment and embodiment 4 is that the addition amount of the composite steel slag powder admixture is 25 g, the addition amount of ferroaluminate cement is 75 g, and other conditions remain the same.

[0083] Example 9

[0084] The difference between this embodiment and embodiment 4 is that the addition amount of the composite steel slag powder admixture is 30 g, the addition amount of the ferroaluminate cement is 70 g, and other conditions remain the same.

[0085] Comparative Example 4

[0086] The difference between this embodiment and embodiment 4 is that no composite steel slag powder admixture is added, the addition amount of ferroaluminate cement is 100 g, and other conditions remain the same.

[0087] Water penetration resistance test: Referring to GB / T 50082-2009 standard, the water penetration height method is used to test the water penetration resistance of concrete. The concrete is made into a truncated cone with an upper inner diameter of 180mm, a lower inner diameter of 190mm, and a height of 250mm. It is placed in a concrete permeameter for water penetration resistance test with a water pressure of 1.5MPa.

[0088] Electric flux test: Referring to GB / T 50082-2009 standard, the concrete was prepared into a sample with a diameter of 100 mm and a height of 50 mm. The electric flux of the concrete sample was tested using a concrete chloride ion electric flux meter. The experimental solution was a 3% NaCl solution.

[0089] Table 3 Impermeability and corrosion resistance test

[0090]

[0091] With the increase of the content of steel slag-based composite admixtures, the impermeability and chloride ion resistance of concrete are enhanced. This is because the addition of steel slag-based composite admixtures makes the system composed of complex particles. Compared with single cement particles, particles of different sizes enter the concrete, changing the pore structure of the concrete, reducing its porosity and making the pore distribution more uniform, which can make the system structure more densely filled; steel slag-based composite admixtures, fluorine-containing quaternary ammonium salt siloxane modifiers and modified basalt fibers have a synergistic effect, forming a spatial network structure, which can make the structure of concrete more compact, increase the impermeability of concrete, and further broaden the application range of concrete.

[0092] The above embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the patent application. It should be pointed out that, for ordinary technicians in this field, several modifications and improvements can be made without departing from the concept of the present application, which all belong to the protection scope of the present application; the methods used in the present application are conventional methods unless otherwise specified.

Claims

1. A seawater-resistant ferroaluminate cement concrete, characterized in that: The ferroaluminate cement concrete comprises the following components in parts by weight: 70-90 parts of ferroaluminate cement, 10-30 parts of composite steel slag powder admixture, 230-280 parts of crushed stone, 180-210 parts of quartz sand, 15-30 parts of fly ash, 5-8 parts of polycarboxylate high-efficiency water reducing agent, 2-5 parts of admixture, 1-5 parts of modified basalt fiber, 2-10 parts of fluorine-containing quaternary ammonium salt siloxane modifier and 40-50 parts of deionized water; The preparation method of the composite steel slag micropowder admixture is as follows: steel slag, slag and zeolite are mixed in a mass ratio of 25:65:10, and an appropriate amount of deionized water is added to control the solid content to 40-45%, and an intermittent ball mill is used for grinding at 40-60° C. to a median particle size of ≦5 μm, carboxymethyl cellulose and an activator are added, and stirred at room temperature for 15-30 minutes to obtain the composite steel slag micropowder admixture; the activator is a mixture of sodium sulfate, triisopropanolamine and silica gel powder, and the mass ratio of the three is 2:2:

1.

2. The seawater erosion resistant ferroaluminate cement concrete and its preparation method according to claim 1, characterized in that: The additive is any one of 2-phospho-1,2,4-tricarboxylic acid butane, sodium gluconate, and hydroxyethylidene diphosphonic acid.

3. The seawater erosion resistant ferroaluminate cement concrete according to claim 1, characterized in that: The preparation method of the modified basalt fiber is as follows: 10g of basalt fiber, 2g of KH560 and 30mL of ethanol are uniformly dispersed by ultrasonication, reacted at 60°C for 3h, and centrifuged and dried to obtain the modified basalt fiber.

4. The seawater erosion resistant ferroaluminate cement concrete according to claim 1, characterized in that: The preparation method of the fluorine-containing quaternary ammonium salt siloxane modifier is: Step (1), under a nitrogen atmosphere, add bis[3-(trimethoxysilyl)propyl]amine and methanol to a reaction flask, stir evenly, add perfluorohexylethylene, stir to react, and after the reaction is completed, concentrate under reduced pressure and dry to obtain a fluorine-containing siloxane monomer; Step (2), under a nitrogen atmosphere, add a fluorinated siloxane monomer and N,N-dimethylformamide to a reaction flask, stir evenly, add 3-bromopropylene, react at 80-100° C. for 16-24 hours, cool to room temperature, filter, wash with deionized water, and dry to obtain an alkenyl fluorinated siloxane monomer; Step (3), under a nitrogen atmosphere, add methyl methacrylate, acrylic acid, 2-acrylamide-2-methacrylic acid, alkenyl fluorine-containing siloxane monomer and deionized water into a reaction flask, stir evenly, dissolve potassium persulfate in deionized water to prepare an initiator solution with a mass fraction of 30-40%, and add dropwise at a speed of 2-3.5 mL / min. After the addition is completed, react at 70-85° C. for 1-3 h, cool to 35-45° C., add sodium bicarbonate aqueous solution to adjust the pH to neutral, and obtain a fluorine-containing quaternary ammonium salt siloxane modifier.

5. The seawater erosion resistant ferroaluminate cement concrete according to claim 4, characterized in that: In the step (1), the molar ratio of bis[3-(trimethoxysilyl)propyl]amine to perfluorohexylethylene is 1:1.05-1.

2.

6. The seawater erosion resistant ferroaluminate cement concrete according to claim 4, characterized in that: In the step (1), the reaction temperature is 45-60° C. and the reaction time is 5-12 h.

7. The seawater erosion resistant ferroaluminate cement concrete and its preparation method according to claim 4, characterized in that: In the step (2), the molar ratio of the fluorinated siloxane monomer to 3-bromopropylene is 1:1.1-1.

4.

8. The seawater erosion resistant ferroaluminate cement concrete according to claim 4, characterized in that: In the step (3), the mass ratio of methyl methacrylate, acrylic acid, 2-acrylamide-2-methylacrylic acid, alkenyl fluorinated siloxane monomer and potassium persulfate is 100:10-20:8-15:3-12:4-8.

9. A method for preparing seawater-resistant alumina-ferrocement concrete according to any one of claims 1 to 8, characterized in that: The preparation method comprises the following steps: pouring ferroaluminate cement, composite steel slag powder admixture, crushed stone, quartz sand and fly ash into a concrete mixer and dry mixing for 50-80 seconds, adding admixture, polycarboxylate water reducer and deionized water after mixing evenly, mixing and stirring for 5-10 minutes, then adding modified basalt fiber and fluorine-containing quaternary ammonium salt siloxane modifier, stirring for 10-20 minutes, and injecting into a mold after mixing evenly, vibrating for 20-40 seconds, smoothing with a spatula, standing for 16-24 hours, demoulding, and placing in a steam curing box for steam curing to obtain ferroaluminate cement concrete resistant to seawater erosion.

10. The method for preparing seawater erosion resistant ferroaluminate cement concrete according to claim 9, characterized in that: The steam curing process is to firstly cure at room temperature for 5-8 hours, then cure at a constant temperature of 50-65°C for 12-16 hours, and finally naturally cure for 7-10 days.

Citation Information

Patent Citations

  • Composite micro-powder made of mineral slag and steel slag

    CN102765897A

  • Concrete taking industrial waste residues as admixture and preparation method thereof

    CN110981356A

  • Modified production preparation method of composite mineral admixture

    CN111268934A

  • Fluorosiloxane polyolefin copolymer and preparation method thereof

    CN112898508A

  • Impact-resistant and wear-resistant concrete for rapid road repair and preparation process of impact-resistant and wear-resistant concrete

    CN115521118A

Cited By

  • High-crack-resistance long-service-life concrete product and preparation method thereof

    CN120157428A

  • Riprap for sea reclamation and preparation method thereof

    CN120864850A

  • A riprap for reclamation and a method for preparing the same

    CN120864850B